2012
DOI: 10.2116/analsci.28.257
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study on the Electrochemical Reduction of 9,10-Anthraquinone in the Presence of Hydrogen-bond and Proton Donating Additives

Abstract: The electrochemical reduction of 9,10-anthraquinone (AQ) was investigated in CH3CN in both the absence and presence of the hydrogen-bond and proton donating additives, CH3OH, CH(CF3)2OH, phenol, 4-methoxyphenol, 4-cyanophenol, 2,4,6-trichlorophenol, and benzoic acid (BA). Three clearly different types of electrochemical behavior were observed with increasing concentrations of the additives, and were simulated to analyze the reaction mechanisms. Type I was observed for weakly interacting additives, such as CH3O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
5
20
0
1
Order By: Relevance
“…This is a consequence of the increase in electron density at the oxygen atoms after each reduction reaction permitting stronger hydrogen bonds to be formed between the DH compounds and acceptor Q 2À as compared to QC À and Q molecules. With that knowledge, the electrochemistry of quinones has been 1) used as an assessment of their own hydrogen-bond-acceptor ability [13] and 2) applied as measures of the hydrogen-bond-donor ability of alcohols, [13a-e, 14] polyalcohols, [13d,e] phenols, [14] and amides [15] in aprotic organic solvents, as well as for quantifying trace moisture. [13f, 16] Further studies have shown that the magnitudes of the potential shifts are dependent on the electronic and steric effects of the various quinone forms (Q, QC À and Q 2À ), the specific DH compounds, as well as the type of solvent [16] and supporting electrolyte [16b, 17] employed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a consequence of the increase in electron density at the oxygen atoms after each reduction reaction permitting stronger hydrogen bonds to be formed between the DH compounds and acceptor Q 2À as compared to QC À and Q molecules. With that knowledge, the electrochemistry of quinones has been 1) used as an assessment of their own hydrogen-bond-acceptor ability [13] and 2) applied as measures of the hydrogen-bond-donor ability of alcohols, [13a-e, 14] polyalcohols, [13d,e] phenols, [14] and amides [15] in aprotic organic solvents, as well as for quantifying trace moisture. [13f, 16] Further studies have shown that the magnitudes of the potential shifts are dependent on the electronic and steric effects of the various quinone forms (Q, QC À and Q 2À ), the specific DH compounds, as well as the type of solvent [16] and supporting electrolyte [16b, 17] employed.…”
Section: Introductionmentioning
confidence: 99%
“…At present, almost all information about the hydrogen-bonding ability of DH compounds obtained by using the electrochemistry of quinones has been derived with the single global equilibrium model [13][14][15][16] or the model involving equilibria in n and m successive stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent comprehensive studies related to the voltammetric features performed with water-soluble quinones and coenzyme Qs in buffered and non-buffered aqueous media probably gave best explanations about the disputed redox behavior of these systems [41][42][43][44]. In fact, many authors claimed that the redox chemistry of coenzyme Qs and quinones from water solutions is always linked to a mechanism in which free radical intermediates are involved [see 2, 9, and 33, for example].…”
Section: Voltammetry Of Coenzyme Qs In Buffered and Non-buffered Aquementioning
confidence: 99%
“…Keeping in mind all the possible redox transformations in which CoQs are undergoing in both aprotic or aqueous media [2,9,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], several relevant theoretical models can be applied to describe their voltammetric behavior. In the last few years, several groups worked on the development of mathematical models of coupled redox reactions under conditions of cyclic and square-wave voltammetry.…”
Section: Theoretical Studies Relevant To the Coenzyme Q's Redox Chemimentioning
confidence: 99%